2019
DOI: 10.1177/0198742919888758
|View full text |Cite
|
Sign up to set email alerts
|

Examining the Generalization of a Combined Independent and Interdependent Group Contingency for Students With Emotional and Behavioral Disorders

Abstract: Using an ABAB withdrawal design, the study evaluated the direct and generalized effects of a combined independent and interdependent group contingency on the engagement and disruptive behavior of two groups of students enrolled in an alternative school serving students with emotional and behavioral disorders. Class 1 included seven middle school students and Class 2 included eight high school students. For both classes, systematic direct observation behavior data were collected both in the targeted class perio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…The results agree with those obtained from the reviewed literature, where it was found that the most effective schools are those with a well-organised environment and high academic expectations (Hawkins et al, 2020). Also, it was shown that students in classrooms where materials are organised and accessible have fewer disruptive behaviours than those in classrooms where materials are disorganised and in disarray (David-Ferdon, 2021).…”
Section: Response Ratesupporting
confidence: 89%
“…The results agree with those obtained from the reviewed literature, where it was found that the most effective schools are those with a well-organised environment and high academic expectations (Hawkins et al, 2020). Also, it was shown that students in classrooms where materials are organised and accessible have fewer disruptive behaviours than those in classrooms where materials are disorganised and in disarray (David-Ferdon, 2021).…”
Section: Response Ratesupporting
confidence: 89%
“…Attachment and Biobehavioral Catch-Up (ABC) (Dozier & Bernard 2019) is a 10-session home visiting program designed to enhance parental nurturance when the infant is distressed, enhance sensitivity when the infant is not distressed, and decrease frightening and harsh behaviors at all times. The intervention is implemented in the home because generalization of behaviors learned is most successful when behaviors are learned and practiced in the environment in which they will be implemented (e.g., Hawkins et al 2020). In addition, giving feedback regarding behaviors in the moment provides parents with repeated practice in intervention target behaviors; such feedback has been demonstrated to increase these target behaviors (Lieneman et al 2017).…”
Section: Interventions Attachment and Biobehavioral Catch-upmentioning
confidence: 99%
“…However, behavior change that only occurs in the training setting has low value when thinking of improving the quality of education and by extension life for students with EBD. According to Hawkins et al (2020), the issue of the generalization of intervention effects is particularly important for children with EBD who often engage in problem behaviors in a variety of settings. To make the largest impact on the lives of those with EBD, we need to plan and implement generalization tactics with our students and provide ample opportunities for the behaviors to be practiced in a variety of settings.…”
mentioning
confidence: 99%